2002
DOI: 10.1017/s001667230100547x
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance genes induce a mating competition cost in Culex pipiens mosquitoes

Abstract: Resistance to organophosphorus insecticides (OP) in Culex pipiens mosquitoes represents a convenient model for investigating the fitness cost of resistance genes and its origin, since both the environmental changes in nature and the adaptive genes are clearly identified. Two loci are involved in this resistance--the super-locus Ester and the locus Ace.1--each displaying several resistance alleles. Population surveys have shown differences in fitness cost between these resistance genes and even between resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
200
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(210 citation statements)
references
References 37 publications
8
200
2
Order By: Relevance
“…Until now, reversion to susceptibility has often been observed in laboratory or field populations of insects, and fitness costs or deleterious effects of resistance genes have been observed (mosquito Culex pipiens: Berticat et al, 2002;Berticat et al, 2004;Bourguet et al, 2004 : Foster et al, 2003;Foster et al, 2005). If resistance factors have disadvantageous effects on fitness, it is expected that the frequencies of resistance factors within insect populations tend to decrease under no insecticide environments, which results in the tendency towards a decrease in levels of resistance to insecticides within insect populations (Crow, 1957).…”
Section: Resultsmentioning
confidence: 99%
“…Until now, reversion to susceptibility has often been observed in laboratory or field populations of insects, and fitness costs or deleterious effects of resistance genes have been observed (mosquito Culex pipiens: Berticat et al, 2002;Berticat et al, 2004;Bourguet et al, 2004 : Foster et al, 2003;Foster et al, 2005). If resistance factors have disadvantageous effects on fitness, it is expected that the frequencies of resistance factors within insect populations tend to decrease under no insecticide environments, which results in the tendency towards a decrease in levels of resistance to insecticides within insect populations (Crow, 1957).…”
Section: Resultsmentioning
confidence: 99%
“…Mating efficiency was inversely proportional to the temephos resistance ratio. Using a different approach, Berticat et al (2002) demonstrated that OP resistance significantly affects the insemination rate of Cx. pipiens, resistant males being less competitive.…”
Section: Discussionmentioning
confidence: 99%
“…Several parameters of insect biology can be affected by pesticide resistance, such as development time, adult longevity, behaviour, reproduction and the immune system (Berticat et al 2002, Rivero et al 2010. Once altered, these aspects have the potential to influence both the dynamics of insecticide resistance dissemination and the relationship among vectors and the parasites they transmit.…”
mentioning
confidence: 99%
“…Four strains sharing the same genetic background and only differing by their genotype at Ester and/or ace-1 locus were used: the insecticide-susceptible strain S-LAB, homozygous for ace-1 S and Ester 0 (Georghiou et al, 1966) ; the resistant strains SA1 and SA4, homozygous for ace-1 S and for the resistance alleles Ester 1 and Ester 4 , respectively ; and finally, the resistant strain SR, homozygous for Ester 0 and for the resistance allele ace-1 R (Berticat et al, 2002 a). Before all experiments, all strains were reared under the same standardized conditions for a minimum of 5 generations, preventing possible maternal effects.…”
Section: (I) Mosquito Strainsmentioning
confidence: 99%